PENGARUH PERHATIAN, PEMAHAMAN DAN INGATAN AKUNTAN TERHADAP PENERAPAN AKUNTANSI SUMBER DAYA MANUSIA (Studi Pada Para Akuntan di Kota Malang dan Surabaya) - Surenggono, Surenggono (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2005)
The purpose of this study is to analyze the influence of attention, comprehension and retention of accountant toward the implementation of Human Resources Accounting whether it is in individual or even in together. Research sample are Accountants that working at Malang and Surabaya City by respondents that consist of many accountants. They are public accountant, educator accountant and intern accountant. Measurement used in this study has perceptional characteristics. Correlation analysis used in this study is to examine the relation between independent and dependent variables, and multiple regression analysis to know the influence of independent and dependent variables. The result of 1st 2nd and 3th hypothesis examination can be known that in partial there is any significant relation between independent variabel that is attention (Xl), comprehension (X2) and retention (X3) toward dependent variable that is implementation of Human Resources Accounting (Y). From the result of fourth hypothesis, by using F-test, that simultaneously there is any significant relationship independent variable, that is attention (Xl), comprehension (X2) and retention (X3) toward dependent variable, that is the implementation of Human Resources (Y). From the result of analysis, it can be known that the most dominant independent variables that influence dependent variable is comprehension variable (by the assumption of other variable that has constant characteristics).